The combination of phase angle and age has a good diagnostic value for sarcopenia in continuous ambulatory peritoneal dialysis patients - Chen, Ye; Wu, Jinlan; Ran, Lei; Yu, Dan; Chen, Xi; Liu, Maodong (Frontiers in Nutrition, 2022)
Aims: There are limited studies on phase angle and sarcopenia in continuous ambulatory peritoneal dialysis patients. So, we want to explore the association between phase angle and sarcopenia and find a more sensitive indicator for diagnosing sarcopenia. Methods: We included 101 continuous ambulatory peritoneal dialysis patients from March 2022 to August 2022 and measured the phase angle and body composition by bioelectrical impedance analysis. All patients had their handgrip strength measured. Then, we divided patients into the sarcopenia (n=30) group and non-sarcopenia(n=71) group according to the sarcopenia diagnostic strategy formulated by the Asian Working Group for Sarcopenia. We used logistic regression to explore the risk factors of sarcopenia. We applied Receiver-operating characteristics curves to determine the diagnostic accuracy of these risk factors. Results: After adjustments for sex, age, diabetes, BMI, extracellular water ratio, extra water, serum creatinine, total kt/v, and residual kt/v, phase angle correlated to handgrip strength and lowered limb muscle mass but not to skeletal muscle mass, upper arm muscle circumference, upper limb muscle mass and appendicular skeletal muscle mass index. In the multivariate logistic model, low phase angle and older age are risk factors for sarcopenia. The AUROC of phase angle for sarcopenia is 0.79(95%CI, 0.70-0.86, P＜0.01) for both sexes, 0.70 and 0.85 for females and males. After we combined age and phase angle as diagnostic indicators of sarcopenia, the AUROC is 0.91(95%CI, 0.83-0.96, P＜0.0001) in both sexes, 0.89 and 0.93 for females and males. Conclusion: This study illustrates that age 52 or older is an independent risk factor for sarcopenia in continuous ambulatory peritoneal dialysis patients. Phase angle can act as a predictor of sarcopenia in those patients. But the combination of age and phase angle is more valuable in diagnosing sarcopenia.